Alpha-actinin-3 deficiency does not significantly alter oxidative enzyme activity in fast human muscle fibres - Vincent, B.; Windelinckx, A.; Van Proeyen, K.; Masschelein, E.; Nielens, H.; Ramaekers, M.; Van Leemputte, M.; Hespel, P.; Thomis, M. (Acta Physiologica, 2012)
Aim:  In Western European populations, about 18% of all individuals have a complete deficiency of the alpha‐actinin‐3 protein owing to homozygosity for a stop codon mutation (R577X) in the ACTN3 gene. Actn3−/− knock‐out mice show increased activity of multiple enzymes in the aerobic metabolic pathway in fast muscle fibres. Whether this observation is also present in human XX genotype carriers compared to RR carriers has not been studied in a fibre‐type‐specific approach in humans. The purpose of this study was therefore to compare fibre‐type‐specific oxidative enzyme activity in humans with a different ACTN3 R577X genotype. Methods:  Vastus lateralis muscle biopsy samples of 17 XX and 16 RR subjects were used to measure markers of oxidative capacity [cytochrome c oxidase (CYTOX) and succinate dehydrogenase (SDH)] in a fibre‐type‐specific assay using enzyme histochemistry. Results:  Cytochrome c oxidase staining showed no significant genotype group differences in type I or type II muscle fibres. Also, we found no significant differences in SDH staining of fast fibres comparing XX and RR carriers. Conclusion:  In conclusion, the increase in oxidative enzyme activity of fast muscle fibres, as reported in an Actn3−/− knock‐out mouse, was not observed in our human samples. Known differences in metabolic characteristics of muscle fibres in rodents compared to humans may in part explain this discrepancy in findings.